THERMODYNAMICS AN ENGINEERING APPROACH - Çengel, Yunus A.; Boles, Michael A.; Kanoğlu, Mehmet (McGraw Hill, 2024)
Cengel's Thermodynamics is known to be student friendly, self-instructive, and easy to read and understand even for the most challenging topics with the help of attractive illustrations, examples, and real-world applications. The authors' philosophy is that the best way to learn is by practice. Special effort is made throughout the book to reinforce material that was presented earlier and to appeal to students' natural curiosity and intuition. For instructors looking to engage students and enhance their problem-solving skills, Connect offers student-friendly, accessible content, tools, and resources that develop high-level problem-solving and critical thinking skills, including New Application-Based Activities.